PENGARUH CITRA PERUSAHAAN, KUALITAS PELAYANAN DAN PERSONAL SELLING TERHADAP KEPUASAN PELANGGAN (STUDI KASUS DI PT HOLCIM BETON CABANG KEMBANGAN) - Gusli Chidir (Journal Of Communication Education, 2015)
ABSTRACTThe rapid competition concrete industry in Indonesia is not only due to rising incomes and a growingeconomy, but also because customers are increasingly savvy and demanding. Responding to the PT HolcimBeton continues to improve its services both from HR and supporting systems such as SAP systems., Howeverthe opposite phenomenon is found where, according to a survey conducted independent research emerge on theinitiative of Holcim Beton which is found that the value of customer satisfaction continues to decline from 2009until 2011, which caused several factors namely Corporate Image, Service Quality and Personal Selling. Of thisphenomenon and the author tries to investigate the company over the decline in customer satisfaction, in thiscase the authors used survey method using questionnaires. The results showed that the correlation between thevariables Corporate Image, Service Quality, and Personal Selling to variable Customer Satisfaction is verystrong.Suggestions in this study were PT Holcim Beton should really keep the Corporate Image by conductingactivities related to the surrounding community, quality of service too should all involved parties both from themanagement down to the employees as well as Personal selling should be more attuned to the activities ongoingtraining that is integrated with the customer.Keywords: Corporate Image, Service Quality, Personal Selling and Customer Satisfaction.